Knowledge of gym goers on myths and truths in resistance training - Alexandra Unger; Clemens Mosgan; Christofer Wolte; Sara Pettauer; Jan Wilke (Scientific Reports)
Abstract Over the last decades, resistance training (RT) has experienced a surge in popularity, and compelling evidence underpins its beneficial effects on health, well-being, and performance. However, sports and exercise research findings may translate poorly into practice. This study investigated the knowledge of Austrian gym-goers regarding common myths and truths in RT. Based on topical systematic reviews (n = 45), a digital questionnaire with 14 statements on RT methods and practices, randomly phrased as myths or truths, was administered to Austrians exercising in local fitness centres. Chi-squared tests were used to check if a majority correctly identified true and false statements. A total of n = 721 (30.1 ± 14 years, 454 males) out of n = 790 contacted individuals completed the survey (response rate: 91.2 percent). Five out of fourteen statements (truth: protein augments strength and hypertrophy, creatine augments strength, superiority of full- vs. partial-ROM RT for hypertrophy; myth: RT reduces flexibility, low-load, high-volume RT is as effective as high-load RT with regard to maximal strength) were identified correctly by a majority (p < .01). The awareness of the scientific evidence on RT is low among gym-goers. Upcoming studies should be geared to improve science communication.